Technology for results : developing service-based plans - Mayo, Diane, 1950- (PLA results series., 2005)
"As the latest entry in the Public Library Association's best-selling Results Series, Technology for Results will enhance the effectiveness of current library technologies and ensure that new investments support the library's mission." "Building from the proven process outlined in The New Planning for Results, this step-by-step guide helps librarians and administrators create an actual blueprint for results." "Professional librarian and library automation expert Diane Mayo shows librarians how to create a dynamic technology plan that will allocate resources to support library priorities and manage technology services based on community goals. And with the help of fourteen workforms, librarians can customize the planning process to sustain effective technology programs while expanding and adding where needed." "Technology for Results provides the must-have answers for addressing fast-changing technology issues while meeting the library's strategic objectives. No public library can afford to be without it."--Jacket.